Precious metal catalyst, screening method thereof and membrane electrode

By controlling the XRD spectrum of the precious metal catalyst and the ECSA difference screening method, the problem of uneven particle size distribution of the platinum-carbon catalyst was solved, the activity and durability of the catalyst were improved, and it is suitable for hydrogen fuel cells.

CN120662548APending Publication Date: 2025-09-19SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510867216.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

In the existing technology, the particle size distribution of platinum-carbon catalysts is uneven, resulting in reduced catalytic activity and durability. In particular, the dissolution and agglomeration problems of small particles are difficult to effectively solve, affecting the performance of hydrogen fuel cells.

Method used

By controlling the difference between the first half-width of the diffraction peak corresponding to the (111) crystal plane in the XRD spectrum of the precious metal catalyst and the second half-width of the Gaussian function fitting to be less than 0.4 degrees, and controlling the difference between the theoretical and measured ECSA within a certain range, precious metal catalysts with uniform particle size are screened out.

Benefits of technology

Low-cost and rapid screening of precious metal catalysts was achieved, and catalysts with uniform particle size and few large particles were obtained, which improved the catalytic activity and durability and are suitable for hydrogen fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662548A_ABST
    Figure CN120662548A_ABST
Patent Text Reader

Abstract

A noble metal catalyst, a screening method thereof and a membrane electrode belong to the field of hydrogen fuel cells. The screening method of the noble metal catalyst comprises the following steps: selecting the noble metal catalyst from a platinum elementary substance catalyst, a gold elementary substance catalyst, a palladium elementary substance catalyst, a platinum-carbon catalyst, a gold-carbon catalyst or a palladium-carbon catalyst; the method comprises the following steps: obtaining a first full width at half maximum of a diffraction peak corresponding to a crystal plane (111) of noble metal, obtaining a second full width at half maximum of a diffraction peak corresponding to the crystal plane (111) fitted by a Gaussian function, and screening out the noble metal catalyst meeting the XRD spectrogram requirement according to the condition that the difference value between the first full width at half maximum and the second full width at half maximum is less than 0.4 degree. According to the screening method, the noble metal catalyst with few large noble metal particles and uniform particle size can be obtained through low-cost and rapid screening, and the noble metal catalyst has good catalytic activity and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hydrogen fuel cells, and more specifically, to a noble metal catalyst and a screening method thereof, and a membrane electrode. Background Art

[0002] Platinum-carbon (Pt / C) catalysts are the primary catalyst type currently used in commercial hydrogen fuel cell vehicles due to their higher catalytic efficiency compared to other metal catalysts. However, particle size and distribution significantly impact their service life. Particles of different sizes differ in chemical potential. Smaller NPs (nanoparticles) tend to dissolve in the electrolyte and redeposit on larger particles, increasing particle size and resulting in a loss of active surface area.

[0003] Because the catalyst reacts only on the particle surface, as the platinum particle size increases, the proportion of surface-exposed platinum atoms decreases, significantly reducing the specific activity (SA) and utilization rate of the platinum / carbon catalyst. In particular, when the platinum particle size distribution is too large, the dissolution tendency of small particles increases, leading to a variety of problems such as particle agglomeration and difficulty in desorbing oxygen-containing intermediates, which further reduce the catalyst activity. Therefore, in order to obtain a high-performance and stable catalyst, it is important to avoid a large catalyst particle size distribution and minimize the amount of large-size platinum particles.

[0004] In the prior art, TEM, small-angle X-ray scattering, and other methods are used to statistically analyze the standard deviation of platinum particle size. When the standard deviation is small, it indicates that the platinum particle size distribution is uniform. However, these conventional characterization methods have limitations in describing the particle size distribution. Summary of the Invention

[0005] The present application provides a precious metal catalyst, a screening method thereof, and a membrane electrode. The screening method can quickly screen and obtain precious metal catalysts with few large metal particles and relatively uniform particle size at low cost, and the precious metal catalyst has good catalytic activity and durability.

[0006] The implementation method of this application is achieved as follows: In a first aspect, the present application provides a method for screening a precious metal catalyst, which comprises: Obtain an XRD spectrum of the noble metal catalyst, wherein the noble metal catalyst is selected from a platinum catalyst, a gold catalyst, a palladium catalyst, a platinum-carbon catalyst, a gold-carbon catalyst or a palladium-carbon catalyst.

[0007] According to the XRD spectrum, the first half-width of the diffraction peak corresponding to the (111) crystal plane of the noble metal, the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function, and the difference between the first half-width and the second half-width are obtained; Among them, according to the difference between the first half-height width and the second half-height width being less than 0.4 degrees, the precious metal catalysts that meet the XRD spectrum requirements are screened out.

[0008] The screening method for the above-mentioned precious metal catalyst provided in the present application controls the difference between the first half-width of the diffraction peak corresponding to the (111) crystal plane of the precious metal and the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function to be less than 0.4 degrees, thereby enabling low-cost and rapid screening to obtain precious metal catalysts with few large metal particles and relatively uniform particle size, and the precious metal catalyst has good catalytic activity and durability.

[0009] In some optional embodiments, the screening method further includes: obtaining the theoretical ECSA, measured ECSA, and the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst that meets the XRD spectrum requirements; wherein, the precious metal catalyst that meets the requirements is screened out based on the absolute value of the difference between the theoretical ECSA and the measured ECSA divided by the theoretical ECSA being less than 5%.

[0010] In some optional embodiments, the noble metal catalyst is a platinum-carbon catalyst, and the loading mass of platinum in the platinum-carbon catalyst is 40%-65%.

[0011] In some optional embodiments, the specific surface area of ​​the platinum-carbon catalyst is 400 m² / g-1000 m² / g.

[0012] In a second aspect, the present application provides a precious metal catalyst, which includes a platinum catalyst, a gold catalyst, a palladium catalyst, a platinum-carbon catalyst, a gold-carbon catalyst, or a palladium-carbon catalyst.

[0013] In the XRD spectrum of the precious metal catalyst, the diffraction peak corresponding to the (111) crystal plane of the precious metal has a first half-width, and the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function has a second half-width, and the difference between the first half-width and the second half-width is less than 0.4 degrees.

[0014] The precious metal catalyst provided in the present application controls the difference between the first half-width at half-maximum of the diffraction peak corresponding to the (111) crystal plane of the precious metal and the second half-width at half-maximum of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function to be less than 0.4 degrees. The precious metal catalyst has few large-particle metal particles and a relatively uniform particle size. The precious metal catalyst has good catalytic activity and durability.

[0015] In some optional embodiments, the absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA is less than 5%.

[0016] In some optional implementations, the difference between the first full width at half maximum and the second full width at half maximum is less than or equal to 0.2 degrees.

[0017] In some optional embodiments, the absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA is less than or equal to 3%.

[0018] By controlling the difference between the first half-height width and the second half-height width or the absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA within the above range, the precious metal catalyst has better catalytic activity and durability.

[0019] In some optional embodiments, the noble metal catalyst is a platinum-carbon catalyst, wherein the average particle size of the platinum particles is 2.5 nm-4 nm.

[0020] In some optional embodiments, the loading mass of platinum in the platinum-carbon catalyst is 40%-65%.

[0021] In some optional embodiments, the specific surface area of ​​the platinum-carbon catalyst is 400 m² / g-1000 m² / g.

[0022] The third aspect of the present application provides a membrane electrode, which includes a precious metal catalyst obtained by screening using the screening method provided in the first aspect of the present application, or the precious metal catalyst provided in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 is the XRD spectrum of platinum-carbon catalyst sample 1 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function; Figure 2 is the XRD spectrum of platinum-carbon catalyst sample 2 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function; Figure 3 is the XRD spectrum of platinum-carbon catalyst sample 3 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function; Figure 4 is the XRD spectrum of platinum-carbon catalyst sample 4 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function; Figure 5is the XRD spectrum of platinum-carbon catalyst sample 5 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function; Figure 6 The XRD spectrum of platinum-carbon catalyst sample 6 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function; Figure 7 TEM image of platinum-carbon catalyst sample 1; Figure 8 This is the CV diagram of platinum-carbon catalyst sample 1 before and after ADT durability. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with the embodiments, but it will be understood by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the embodiments, if specific conditions are not specified, the conditions according to normal conditions or manufacturer recommendations are carried out. Reagents used or instruments that do not specify manufacturers are conventional products that can be purchased commercially.

[0026] The following is a detailed description of the noble metal catalyst, its screening method, and membrane electrode according to the embodiment of the present application: The first aspect of the present application provides a method for screening a precious metal catalyst, which comprises: Obtain an XRD spectrum of the noble metal catalyst, wherein the noble metal catalyst is selected from a platinum catalyst, a gold catalyst, a palladium catalyst, a platinum-carbon catalyst, a gold-carbon catalyst or a palladium-carbon catalyst.

[0027] According to the XRD spectrum, the first half-width of the diffraction peak corresponding to the (111) crystal plane of the noble metal, the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function, and the difference between the first half-width and the second half-width are obtained.

[0028] Among them, according to the difference between the first half-height width and the second half-height width being less than 0.4 degrees, the precious metal catalysts that meet the XRD spectrum requirements are screened out.

[0029] It can be understood that the platinum catalyst, the gold catalyst and the palladium catalyst are all nanoparticles, and the platinum-carbon catalyst, the gold-carbon catalyst and the palladium-carbon catalyst are all corresponding precious metal nanoparticles supported on carbon carriers.

[0030] Among them, gold, platinum, and palladium are all precious metals with a face-centered cubic (FCC) crystal structure. In the FCC structure, the (111) crystal plane is the plane with the closest atomic arrangement and the largest interplanar spacing. Nanoparticles with FCC structure often use the (111) plane as the main exposed surface. Therefore, the difference between the first half-height width and the second half-height width of the (111) crystal plane can be used for precise screening of platinum, gold, or palladium. At the same time, since the diffraction signal of the carbon support does not overlap with the peak position of the (111) peak of the precious metal, it will not cover the diffraction peak corresponding to the (111) crystal plane of the precious metal and basically does not affect the peak intensity of the diffraction peak. Therefore, it is also suitable for precise screening of platinum-carbon catalysts, gold-carbon catalysts, or palladium-carbon catalysts.

[0031] It should be noted that the XRD spectrum of the precious metal catalyst can be tested by referring to relevant technologies, and there are no special requirements for it.

[0032] For example, the XRD spectrum is obtained from a Bruker AXSD8 instrument, the radiation source of which is a Cu target that generates Kα rays; the X-ray wavelength λ is 0.15406 nm; when the instrument is working, the voltage is 40 kV, the current is 40 mA; the initial scanning diffraction angle 2θ (θ is the grazing angle) is 15 o , the end scanning diffraction angle 2θ is 52 o , scanning speed is 5 o / min.

[0033] Full Width at Half Maximum (FWHM): Draw a line parallel to the background at the point of maximum intensity (peak apex) of the X-ray diffraction peak. Find the locations on either side of the peak where the intensity drops to half of the maximum intensity. The difference between these two locations on the abscissa (usually 2θ) is the full width at half maximum (FWHM). Both the first and second full widths at half maximum can be calculated using Origin software based on the diffraction peaks measured by XRD.

[0034] Gaussian function fitting can also be performed based on the diffraction peaks measured by XRD using Origin software to obtain the Gaussian function fitting curve and the half-height width of the diffraction peak corresponding to the (111) crystal plane.

[0035] The difference between the first width at half maximum and the second width at half maximum is less than 0.4 degrees, which means that the second width at half half maximum minus the first width at half half maximum is less than 0.4 degrees.

[0036] In summary, the screening method for the above-mentioned precious metal catalyst provided in the present application controls the difference between the first half-width of the diffraction peak corresponding to the (111) crystal plane of the precious metal and the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function to be less than 0.4 degrees, thereby being able to quickly and cheaply screen and obtain precious metal catalysts with few large metal particles and relatively uniform particle size. The precious metal catalyst has good catalytic activity and durability.

[0037] For example, when the noble metal catalyst is a platinum-carbon catalyst, its preparation method includes but is not limited to the following methods: 1200mg of carbon support and 10g of (MEA)2Pt(OH)6 (Pt content 18wt%) were added to 400g of ethylene glycol solution (water content 10wt%), ultrasonicated for 30 minutes, thoroughly mixed, and then preheated in an 80°C oil bath. 10ml of 1M formic acid solution was added dropwise, refluxed for 1 hour, cooled, filtered, and then dried in an 80°C oven for 12 hours to obtain a platinum-on-carbon precursor catalyst. This halogen-free platinum-on-carbon precursor catalyst, when uniformly dispersed, utilizes the principle of positive and negative charge attraction (the precursor carries a negative charge, while the acid provides a positive charge), resulting in uniform deposition of the platinum precursor on the support surface.

[0038] 0.5-4g of a platinum-on-carbon (PtC) catalyst precursor was placed in a small magnetic boat, which was then placed in a tube furnace. Under a hydrogen atmosphere, the temperature was raised at 5°C / min to 80-100°C, with a hydrogen flow rate of 40ml / min, and a total gas flow rate:catalyst weight ratio of 40:0.5-4. The reduction time was 1-3 hours. After the reduction was complete, a PtC catalyst intermediate was obtained. A portion of the PtC catalyst intermediate was assembled into a half-cell and its actual active area (ECSA) was measured. The ECSA met the requirements of ≥95m² / g, indicating that the PtC catalyst intermediate possessed numerous small Pt nucleation sites (approximately 1-2nm), meeting the preparation requirements. The nucleation rate of the Pt precursor was increased by using a low-temperature, high-reducing atmosphere, where the nucleation rate exceeded the growth rate, ensuring uniform nucleation sites (approximately 1-2nm) on the support surface, paving the way for subsequent heat treatment.

[0039] High temperature treatment: Take 1g of the platinum-carbon catalyst intermediate that meets the preparation requirements, put it into a small magnetic boat, put the small magnetic boat into a tubular furnace, nitrogen atmosphere, 20℃ / min to 600-700℃, nitrogen flow rate is 500ml / min, and the insulation time is 1-3h. After the insulation is completed, a platinum-carbon catalyst is obtained. It can be understood that the particle size uniformity of the platinum-carbon catalyst here is closely related to the reduction state before high temperature treatment. Before high temperature treatment, if the surface of the carbon support is all very small particles with the same particle size, the thermal motion trend of the platinum particles is consistent, which is more conducive to the generation of large particles with uniform size and uniform distribution. On the contrary, if there is already inconsistency in size in the reduced state, then in the subsequent high temperature, the large particles will become larger and larger, resulting in a final poor particle size distribution.

[0040] It is understandable that the above preparation method is only an example, and the preparation method of the precious metal catalyst is not actually limited.

[0041] In some optional embodiments, the screening method further includes: obtaining the theoretical ECSA, measured ECSA, and the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst that meets the XRD spectrum requirements; wherein, the precious metal catalyst that meets the requirements is screened out based on the absolute value of the difference between the theoretical ECSA and the measured ECSA divided by the theoretical ECSA being less than 5%.

[0042] It can be understood that the theoretical ECSA of a noble metal catalyst is usually greater than the measured ECSA of the noble metal catalyst, but there may also be cases where the theoretical ECSA of a noble metal catalyst is smaller than the measured ECSA of the noble metal catalyst. Therefore, the absolute value of the difference between the theoretical ECSA and the measured ECSA is divided by the theoretical ECSA as the difference between the theoretical ECSA and the measured ECSA, that is, the difference between the theoretical ECSA and the measured ECSA = |theoretical ECSA-measured ECSA| / theoretical ECSA <5%.

[0043] The theoretical ECSA is calculated as follows: Electrochemically active surface area (ECSA) refers to the effective area of ​​the catalyst surface that can participate in the electrochemical reaction. The theoretical ECSA is calculated based on the geometric surface area of ​​the catalyst, usually assuming that the catalyst particles are of an ideal shape (such as a sphere) and calculated based on their size and density. The theoretical ECSA is calculated as follows: ECSA theoretical = 4πr 2 *N; where: r is the radius of the catalyst particle, and an average particle size is obtained by collecting the particle sizes of 300 particles in TEM; N is the number of particles in the catalyst. Assuming 1g of catalyst, N = 1g / m (the mass of one particle), m = ρ*V, ρ is the density of platinum metal, and V is the volume of a single particle.

[0044] The actual ECSA test method in this application includes: using an electrochemical workstation model HKCS310H to study the electrochemical properties of the catalyst, and the experimental method is as follows: 1. Polishing of the glassy carbon electrode. Wipe the electrode surface with moistened lens paper to remove dirt and ensure that the electrode surface is smooth. Take a small amount of 0.05 μm Al2O3 suspension on a suede polishing disc, hold the glassy carbon electrode upright, apply force evenly with your elbows, let the glassy carbon electrode move slowly on the velvet surface, and grind the electrode in an "8" shape for 3 minutes. Use a wash bottle filled with deionized water to completely rinse the Al2O3 on the surface of the glassy carbon electrode, place the beaker filled with alcohol in an ultrasonic cleaner, hold the glassy carbon electrode, ultrasonicate for 1 minute, and check whether the glassy carbon surface is mirror-like. Otherwise, replace the alcohol in the beaker and ultrasonicate again until the glassy carbon surface is mirror-like. 2. Catalyst formulation preparation. Accurately weigh approximately 10 mg of catalyst into a 20 mL glass vial. Moisten the solution with 10 μL of deionized water, then add 10 mL of Nafion solution to a catalyst concentration of 1 mg / mL. Sonicate in an ice-water bath for 18 minutes to evenly disperse the slurry. 3. Working Electrode Preparation. Place a clean, dry glassy carbon electrode on a horizontal laboratory bench. Use a pipette to evenly drop 10 μL of the slurry onto the smooth electrode. Mount the electrode on a rotating table at 200 rpm and blow dry under N2. 4. Electrolytic Cell Pretreatment. Deoxygenate a 0.5 M H2SO4 electrolytic cell by passing 300 sccm of N2 through the electrolyte. Nitrogen enters the electrolyte through a glass-covered frit. Continue bubbling nitrogen. For a 0.1 M HClO4 electrolytic cell, pass 300 sccm of O2 through the electrolyte through a glass-covered frit. Continue bubbling oxygen until ready for use. 5. Test Methods. CV test: Place the electrodes in an electrolytic cell to form a three-electrode system. The reference electrode is Hg / Hg2SO4, the counter electrode is a platinum mesh electrode, and the electrolyte is a nitrogen-saturated 0.5 M H2SO4 solution maintained at 25°C. Open the software, set the scan rate to 50 m / s in the CV test window, and scan 20 times (10 cycles) from -0.632 to 0.328 V to fully activate the catalyst and achieve a stable re-desorption peak. Calculate the electrochemically active area (ECSA) of the catalyst using the data from the last cycle.

[0045] Due to the broadening effect of the XRD test itself, the XRD spectrum can only exclude samples with a large number of large metal particles. There is a risk of inaccurate testing for samples with precious metal particles below 1.5nm. Therefore, the precious metal catalysts that meet the XRD spectrum requirements are further combined with the difference between the theoretical ECSA and the measured ECSA being less than 5% to screen out precious metal catalysts that meet the requirements. The precious metal catalysts have few large particles and very small particles on the surface, and the precious metal particles are evenly distributed and uniform in size, with good catalytic activity and durability.

[0046] In some optional embodiments, the noble metal catalyst is a platinum-carbon catalyst, and the loading mass of platinum in the platinum-carbon catalyst is 40%-65%.

[0047] The platinum-carbon catalyst with the above-mentioned loading mass has better catalytic activity. At the same time, due to the high loading mass of platinum, the (111) crystal plane diffraction peak intensity is high, and the background effect can be ignored.

[0048] Illustratively, the loading mass of platinum in the platinum-carbon catalyst is any value of 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, 65%, or between any two values.

[0049] In some optional embodiments, the specific surface area of ​​the platinum-carbon catalyst is 400 m² / g-1000 m² / g.

[0050] The specific surface area is obtained by nitrogen adsorption and BET calculation method. For details, please refer to relevant technologies.

[0051] By controlling the specific surface area of ​​the platinum-carbon catalyst within the above range, the platinum-carbon catalyst can achieve both better activity and stability.

[0052] Illustratively, the specific surface area of ​​the platinum carbon catalyst is any one of 400 m² / g, 410 m² / g, 420 m² / g, 430 m² / g, 440 m² / g, 450 m² / g, 460 m² / g, 470 m² / g, 480 m² / g, 490 m² / g, 500 m² / g, 600 m² / g, 700 m² / g, 800 m² / g, 900 m² / g, and 1000 m² / g, or between any two values.

[0053] In a second aspect, the present application provides a precious metal catalyst, which includes a platinum element catalyst, a gold element catalyst, a palladium element catalyst, a platinum-carbon catalyst, a gold-carbon catalyst or a palladium-carbon catalyst.

[0054] In the XRD spectrum of the precious metal catalyst, the diffraction peak corresponding to the (111) crystal plane of the precious metal has a first half-width, and the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function has a second half-width, and the difference between the first half-width and the second half-width is less than 0.4 degrees.

[0055] Among them, gold, platinum, and palladium are all precious metals with a face-centered cubic (FCC) crystal structure. In the FCC structure, the (111) crystal plane is the plane with the closest atomic arrangement and the largest interplanar spacing. Nanoparticles with FCC structure often use the (111) plane as the main exposed surface. Therefore, the difference between the first half-height width and the second half-height width of the (111) crystal plane can be used for precise screening of platinum, gold, or palladium. At the same time, since the diffraction signal of the carbon support does not overlap with the peak position of the (111) peak of the above-mentioned precious metal, it will not cover the diffraction peak corresponding to the (111) crystal plane of the precious metal and basically does not affect the peak intensity of the diffraction peak. Therefore, it is also suitable for precise screening of platinum-carbon catalysts, gold-carbon catalysts, or palladium-carbon catalysts.

[0056] The difference between the first width at half maximum and the second width at half maximum is less than 0.4 degrees, which means that the second width at half half maximum minus the first width at half half maximum is less than 0.4 degrees.

[0057] In summary, the precious metal catalyst provided in the present application controls the difference between the first half-width of the diffraction peak corresponding to the (111) crystal plane of the precious metal and the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function to be less than 0.4 degrees. The precious metal catalyst has few large-particle metal particles and a relatively uniform particle size. The precious metal catalyst has good catalytic activity and durability.

[0058] Optionally, the precious metal catalyst provided in the second aspect of the present application is a precious metal catalyst obtained by screening using the screening method provided in the first aspect of the present application.

[0059] In some optional embodiments, the absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA is less than 5%.

[0060] On the basis that the difference between the first half-width and the second half-width is less than 0.4 degrees, the absolute value of the difference between the theoretical ECSA and the measured ECSA divided by the theoretical ECSA is further controlled to be less than 5%, indicating that there are few large particles and very small particles on the surface of the precious metal catalyst. At this time, the particle size distribution of the precious metal particles is uniform, the size is uniform, and it has good catalytic activity and durability.

[0061] In some optional embodiments, the difference between the first full width at half maximum and the second full width at half maximum is less than or equal to 0.2 degrees, that is, the second full width at half half maximum - the first full width at half half maximum ≤ 0.2 degrees.

[0062] By controlling the difference between the first half-width and the second half-width within the above range, the noble metal catalyst has better catalytic activity and durability.

[0063] In some optional embodiments, the absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA is less than or equal to 3%.

[0064] By controlling the absolute value of the difference between the theoretical ECSA and the measured ECSA of the noble metal catalyst divided by the theoretical ECSA within the above range, the noble metal catalyst has better catalytic activity and durability.

[0065] In some optional embodiments, the noble metal catalyst is a platinum-carbon catalyst, wherein the average particle size of the platinum particles is 2.5 nm to 4 nm.

[0066] The average particle size of the platinum particles can be calculated based on the Scherrer formula from the XRD spectrum.

[0067] The average particle size of the platinum particles is controlled to be 2.5nm-4nm, and the noble metal particles have good catalytic activity.

[0068] In some optional embodiments, the loading mass of platinum in the platinum-carbon catalyst is 40%-65%.

[0069] The platinum-carbon catalyst with the above-mentioned loading mass has better catalytic activity. At the same time, due to the high loading mass of platinum, the (111) crystal plane diffraction peak intensity is high, the background effect can be ignored, and the first half-height width and second half-height width test are more accurate.

[0070] Illustratively, the loading mass of platinum in the platinum-carbon catalyst is any value of 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, 65%, or between any two values.

[0071] In some optional embodiments, the specific surface area of ​​the platinum-carbon catalyst is 400 m² / g-1000 m² / g.

[0072] By controlling the specific surface area of ​​the platinum-carbon catalyst within the above range, the platinum-carbon catalyst can achieve both better activity and stability.

[0073] Illustratively, the specific surface area of ​​the platinum carbon catalyst is any one of 400 m² / g, 410 m² / g, 420 m² / g, 430 m² / g, 440 m² / g, 450 m² / g, 460 m² / g, 470 m² / g, 480 m² / g, 490 m² / g, 500 m² / g, 600 m² / g, 700 m² / g, 800 m² / g, 900 m² / g, and 1000 m² / g, or between any two values.

[0074] The third aspect of the present application provides a membrane electrode, which includes a precious metal catalyst obtained by screening using the screening method provided in the first aspect of the present application, or the precious metal catalyst provided in the second aspect of the present application.

[0075] The noble metal catalyst, screening method thereof, and membrane electrode of the present application are further described in detail below with reference to the examples.

[0076] Platinum-carbon catalyst samples 1-6 were obtained.

[0077] The preparation method of platinum-carbon catalyst sample 1 includes: (1) 1200 mg of carbon support and 10 g of (MEA)2Pt(OH)6 (Pt content 18 wt%) were added to 400 g of ethylene glycol solution (water content 10 vt%), ultrasonicated for 30 min, thoroughly mixed, and then preheated in an 80 °C oil bath. 10 ml of 1 M formic acid solution was added dropwise, refluxed for 1 h, cooled and filtered, and dried in an 80 °C oven for 12 h to obtain a platinum-carbon precursor catalyst.

[0078] (2) Take 1g of platinum-carbon precursor catalyst and put it into a small magnetic boat. Put the small magnetic boat into a tubular furnace, and heat it to 80℃ (reduction temperature) at 5℃ / min in a hydrogen atmosphere. The hydrogen flow rate is 40ml / min, and the total gas flow rate is: platinum-carbon precursor catalyst mass (40:1). The reduction time is 3h. After the reduction is completed and cooled, a platinum-carbon catalyst intermediate is obtained.

[0079] (3) Take 1g of the platinum-carbon catalyst intermediate and put it into a small magnetic boat. Put the small magnetic boat into a tubular furnace, heat it to 700℃ at 20℃ / min under nitrogen atmosphere, with a nitrogen flow rate of 500ml / min, and keep it warm for 3h. After cooling, obtain platinum-carbon catalyst sample 1.

[0080] The preparation method of platinum-carbon catalyst sample 2 differs from that of platinum-carbon catalyst sample 1 only in that: Step (2): Take 6g of platinum-carbon precursor catalyst and put it into a small magnetic boat, put the small magnetic boat into a tubular furnace, and heat it to 80℃ (reduction temperature) at 5℃ / min in a hydrogen atmosphere. The hydrogen flow rate is 40ml / min, and the total gas flow rate: platinum-carbon precursor catalyst mass is (40:6). The reduction time is 3h. After the reduction is completed and cooled, a platinum-carbon catalyst intermediate is obtained.

[0081] The preparation method of platinum-carbon catalyst sample 3 differs from that of platinum-carbon catalyst sample 1 only in that: Step (2): Take 1g of platinum-carbon precursor catalyst and put it into a small magnetic boat, put the small magnetic boat into a tubular furnace, and heat it to 80℃ (reduction temperature) at 5℃ / min in a hydrogen / nitrogen atmosphere. The hydrogen flow rate is 25ml / min, the nitrogen flow rate is 475ml / min, and the total gas flow rate is: platinum-carbon precursor catalyst mass (500:1). The reduction time is 3h. After the reduction is completed and cold-cut, a platinum-carbon catalyst intermediate is obtained.

[0082] The platinum-carbon catalyst sample 4 is a commercially available platinum-carbon catalyst TEC10EA50E.

[0083] The preparation method of platinum-carbon catalyst sample 5 differs from that of platinum-carbon catalyst sample 1 only in that: Step (2): Take 1g of platinum-carbon precursor catalyst and put it into a small magnetic boat, put the small magnetic boat into a tubular furnace, and heat it to 150℃ at 5℃ / min in a hydrogen atmosphere. The hydrogen flow rate is 40ml / min, and the overall gas flow rate: platinum-carbon precursor catalyst mass is (40:1). The reduction time is 3h. After the reduction is completed and cooled, a platinum-carbon catalyst intermediate is obtained.

[0084] The preparation method of platinum-carbon catalyst sample 6 differs from that of platinum-carbon catalyst sample 1 only in that: Step (2): Take 4 g of platinum-carbon precursor catalyst and put it into a small magnetic boat, put the small magnetic boat into a tubular furnace, and heat it to 80°C at 5°C / min in a hydrogen atmosphere. The hydrogen flow rate is 40 ml / min, and the overall gas flow rate: platinum-carbon precursor catalyst mass is (40:4). The reduction time is 3 h. After the reduction is completed and cooled, a platinum-carbon catalyst intermediate is obtained.

[0085] Example (1) Obtain the XRD spectra of platinum-carbon catalyst samples 1-6 respectively.

[0086] The XRD spectrum is from a Bruker AXS D8 instrument. The radiation source of this instrument is a Cu target that produces Kα radiation; the X-ray wavelength λ is 0.15406 nm; when the instrument is working, the voltage is 40 kV and the current is 40 mA; the initial scanning diffraction angle 2θ (θ is the grazing angle) is 15 o , the end scanning diffraction angle 2θ is 52 o , scanning speed is 5 o / min.

[0087] According to the diffraction peaks measured in the XRD spectrum, the first half-width of the diffraction peak corresponding to the (111) crystal plane of platinum was obtained by calculation using Origin software, and the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function was obtained by Origin software and calculated using Origin software, and the difference between the first half-width and the second half-width was calculated (difference = second half-width - first half-width).

[0088] The results are shown in Table 1 and Figure 1-6 shown.

[0089] Figure 1 The XRD spectrum of platinum-carbon catalyst sample 1 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function. Figure 1The black line in the middle is the original data of platinum-carbon catalyst sample 1. After calculation, the first half-maximum width of the diffraction peak corresponding to the (111) crystal plane is 2.538 degrees. Figure 1 The medium gray smooth line is the Gaussian fitting curve. The data in the table are the relevant parameters of the diffraction peak in the Gaussian fitting curve. Peak 1 in the table is the diffraction peak corresponding to the (111) crystal plane in the Gaussian fitting curve. The second half-height width is 2.701 degrees. Therefore, the difference between the first half-height width and the second half-height width is 2.701-2.538=0.163 degrees.

[0090] Figure 2 The XRD spectrum of platinum-carbon catalyst sample 2 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function. Figure 2 The black line in the middle is the original data of platinum-carbon catalyst sample 2. After calculation, the first half-maximum width of the diffraction peak corresponding to the (111) crystal plane is 1.762 degrees. Figure 2 The medium gray smooth line is the Gaussian fitting curve. The data in the table are the relevant parameters of the diffraction peak in the Gaussian fitting curve. Peak 1 in the table is the diffraction peak corresponding to the (111) crystal plane in the Gaussian fitting curve. The second half-height width is 2.694 degrees. Therefore, the difference between the first half-height width and the second half-height width is 2.694-1.762=0.932 degrees.

[0091] Figure 3 The XRD spectrum of platinum-carbon catalyst sample 3 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function. Figure 3 The black line in the middle is the original data of platinum-carbon catalyst sample 3. After calculation, the first half-height width of the diffraction peak corresponding to the (111) crystal plane is 1.97 degrees. Figure 3 The medium gray smooth line is the Gaussian fitting curve. The data in the table are the relevant parameters of the diffraction peak in the Gaussian fitting curve. Peak 1 in the table is the diffraction peak corresponding to the (111) crystal plane in the Gaussian fitting curve. The second half-height width is 2.844 degrees. Therefore, the difference between the first half-height width and the second half-height width is 2.844-1.97=0.874 degrees.

[0092] Figure 4 The XRD spectrum of platinum-carbon catalyst sample 4 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function. Figure 4 The black line in the middle is the original data of platinum-carbon catalyst sample 4. After calculation, the first half-height width of the diffraction peak corresponding to the (111) crystal plane is 2.107 degrees. Figure 4 The medium gray smooth line is the Gaussian fitting curve. The data in the table are the relevant parameters of the diffraction peak in the Gaussian fitting curve. Peak 1 in the table is the diffraction peak corresponding to the (111) crystal plane in the Gaussian fitting curve. The second half-height width is 2.626 degrees. Therefore, the difference between the first half-height width and the second half-height width is 2.626-2.107=0.519 degrees.

[0093] Figure 5 The XRD spectrum of platinum-carbon catalyst sample 5 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function. Figure 5 The black line in the middle is the original data of platinum-carbon catalyst sample 5. The calculated first half-height width of the diffraction peak corresponding to the (111) crystal plane is 1.448 degrees. Figure 5 The medium gray smooth line is the Gaussian fitting curve. The data in the table are the relevant parameters of the diffraction peak in the Gaussian fitting curve. Peak 1 in the table is the diffraction peak corresponding to the (111) crystal plane in the Gaussian fitting curve. The second half-height width is 2.616 degrees. Therefore, the difference between the first half-height width and the second half-height width is 2.616-1.448=1.168 degrees.

[0094] Figure 6 The XRD spectrum of platinum-carbon catalyst sample 6 and the related parameters of the diffraction peak corresponding to the (111) crystal plane fitted by Gaussian function. Figure 6 The black line in the middle is the original data of platinum-carbon catalyst sample 6. The calculated first half-height width of the diffraction peak corresponding to the (111) crystal plane is 2.688 degrees. Figure 6 The medium gray smooth line is the Gaussian fitting curve. The data in the table are the relevant parameters of the diffraction peak in the Gaussian fitting curve. Peak 1 in the table is the diffraction peak corresponding to the (111) crystal plane in the Gaussian fitting curve. The second half-height width is 2.983 degrees. Therefore, the difference between the first half-height width and the second half-height width is 2.983-2.688=0.295 degrees.

[0095] (2) Measured ECSA: The electrochemical performance of the measured ECSA was obtained by using an electrochemical workstation model HKCS310H to study the platinum-carbon catalyst samples 1-6 and the corresponding platinum-carbon catalyst intermediates in the preparation process of the platinum-carbon catalyst samples 1-6. The experimental method is as follows: 1. Polishing the Glassy Carbon Electrode. Wipe the electrode surface with moistened lens tissue to remove dirt and ensure a smooth surface. Apply a small amount of 0.05 μm Al₂O₃ suspension to a suede polishing pad. Hold the glassy carbon electrode upright, applying even pressure with your elbow, and slowly move the electrode along the suede surface, polishing the electrode in a figure-8 pattern for 3 minutes. Rinse the Al₂O₃ completely from the surface of the glassy carbon electrode with a wash bottle filled with deionized water. Place a beaker filled with alcohol in an ultrasonic cleaner, hold the glassy carbon electrode, and sonicate for 1 minute. Check that the surface is mirror-finished. If not, replace the alcohol in the beaker and sonicate again until the surface is mirror-finished. 2. Catalyst Formulation. Accurately weigh approximately 10 mg of platinum-carbon catalyst into a 20 mL glass bottle. Add 10 μL of deionized water to moisten the solution, followed by 10 mL of Nafion solution to a catalyst concentration of 1 mg / mL. Ultrasonicate in an ice-water bath for 18 minutes to evenly disperse the slurry. 3. Preparation of the Working Electrode. Place a clean and dry glassy carbon electrode on a horizontal laboratory table. Use a pipette to evenly drop 10 μL of the above slurry onto the smooth electrode. Mount the electrode on a rotating table at 200 rpm and blow dry under N2. 4. Electrolytic cell pretreatment. Pass 300 sccm of N2 through a 0.5 M H2SO4 electrolytic cell to deoxygenate. Nitrogen enters the electrolyte through a sand core with a glass cover and continues to flow nitrogen. Pass 300 sccm of O2 through a 0.1 M HClO4 electrolytic cell. Oxygen enters the electrolyte through a sand core with a glass cover and continues to flow oxygen for standby use. 5. Test method. CV test: Place the electrode in the electrolytic cell to form a three-electrode system. Among them, the reference electrode is Hg / Hg2SO4, the counter electrode is a platinum mesh electrode, and the electrolyte is a 0.5 M H2SO4 solution saturated with N2 and kept at a constant temperature of 25 ℃. Open the software, set the scan rate to 50 m / s in the CV test window, and scan 20 times (10 cycles) at -0.632~0.328 V to fully activate the catalyst and make the desorption peak basically stable. The electrochemical active area ECSA of the corresponding catalyst is calculated based on the data of the last cycle as the measured ECSA.

[0096] Theoretical ECSA: Assuming that the catalyst particles are ideally spherical, the theoretical ECSA is calculated as follows: ECSA theoretical = 4πr 2 *N, where: r is the radius of the platinum particle, and an average particle size was obtained by collecting the particle sizes of 300 particles in the TEM; N is the number of platinum particles in the platinum-carbon catalyst. Assuming 1g of catalyst, N = 1g / m (the mass of one particle), and m = ρ*V, where ρ is the density of platinum metal and V is the volume of a single particle.

[0097] The absolute value of the difference between the theoretical ECSA and the measured ECSA was calculated and divided by the theoretical ECSA as the difference between the theoretical ECSA and the measured ECSA, that is, the difference between the theoretical ECSA and the measured ECSA = |theoretical ECSA - measured ECSA| / theoretical ECSA). The results are shown in Table 1.

[0098] (3) ADT durability test: The electrochemical test was carried out in a three-electrode system, using the working electrode prepared in (2) as the working electrode, connected to a CHI 600E (CH Instruments) electrochemical workstation, a Hydroflex hydrogen reference electrode (Gaskatel) as the reference electrode, and a platinum wire coil as the counter electrode. The electrolyte was a 0.1 M HClO4 aqueous solution. Cyclic voltammetry (CV) was carried out at room temperature using a nitrogen-saturated HClO4 solution at a scan rate of 50 mV / s and a potential range of 0.05–1.1 V (vs. reversible hydrogen electrode, VRHE). The electrochemically active specific surface area (ECSA) was calculated by calculating the average charge during hydrogen adsorption and desorption, which was taken as 210 µC / cm². The oxygen reduction reaction (ORR) activity test was carried out at room temperature using an oxygen-saturated HClO4 solution using a rotating disk electrode (RDE) method at a scan rate of 10 mV / s, a rotation rate of 1600 rpm, and a potential range of 0.05–1.1 VRHE. Accelerated durability testing (ADT) was performed at room temperature using an oxygen-saturated HClO4 solution at a rotation rate of 1600 rpm and a scan rate of 0.1 V / s. Cyclic voltammetry (CV) and oxygen reduction reaction (ORR) polarization curves were measured after 20,000 cycles in the potential range of 0.6-1.1 VRHE.

[0099] The test results are shown in Table 1.

[0100] Table 1 Preparation parameters and test results of platinum-carbon catalyst samples 1-6

[0101] According to Table 1, it can be seen that the difference between the first half-width and the second half-width is less than 0.4 degrees and the difference between the theoretical ECSA and the measured ECSA is less than 5%. The ADT durable 42000C desorption ECSA attenuation of the platinum-carbon catalyst samples 1 and 6 is significantly reduced, indicating that the platinum-carbon catalyst samples 1 and 6 have good catalytic activity and durability.

[0102] At the same time, according to Figure 7 , Figure 7 This is the TEM image of platinum carbon catalyst sample 1. Figure 7It can be seen that there are very few large particles and very small particles on the surface of platinum-carbon catalyst sample 1, and the particle size distribution of platinum nanoparticles is uniform and the size is uniform.

[0103] Figure 8 This is the CV diagram of platinum-carbon catalyst sample 1 before and after ADT durability. It can be seen that after the 42000CADT durability test, the desorption ECSA of sample 1 decays to 6.09% ((42.33-39.75) / 42.33), indicating that platinum-carbon catalyst sample 1 has good durability.

[0104] According to the comparison of platinum-carbon catalyst samples 1-6, it can be seen that when the catalyst has a smaller difference between the first half-height width and the second half-height width and the difference between the theoretical ECSA and the measured ECSA of the platinum-carbon catalyst, it has better durability.

[0105] At the same time, according to the data in Table 1, it can be shown that during the preparation process of platinum-carbon catalyst samples 1-3 and 5-6, the overall gas flow rate and catalyst mass ratio have an impact on the particle size of the platinum-carbon catalyst intermediate (the measured ECSA of the platinum-carbon catalyst intermediate of each sample is different), which affects the subsequent particle size distribution of the platinum-carbon catalyst. It also shows that the hydrogen concentration and reduction temperature have an impact on the particle size of the platinum-carbon catalyst intermediate, which will also affect the subsequent particle size distribution of the platinum-carbon catalyst.

[0106] In summary, the screening method for the above-mentioned precious metal catalyst provided in this application, by controlling the difference between the first half-width of the diffraction peak corresponding to the (111) crystal plane of the precious metal and the second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function to be less than 0.4 degrees, can quickly and cheaply screen and obtain precious metal catalysts with few large metal particles and relatively uniform particle size, and the precious metal catalysts have good catalytic activity and durability. At the same time, the precious metal catalysts prepared in this application have few large metal particles and relatively uniform particle size, and have good catalytic activity and durability.

[0107] The above is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, various modifications and variations of the present application are possible. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for screening a noble metal catalyst, characterized in that: include: Obtaining an XRD spectrum of a noble metal catalyst, wherein the noble metal catalyst is selected from a platinum catalyst, a gold catalyst, a palladium catalyst, a platinum-carbon catalyst, a gold-carbon catalyst, or a palladium-carbon catalyst; According to the XRD spectrum, a first half-width of a diffraction peak corresponding to a (111) crystal plane of the noble metal, a second half-width of the diffraction peak corresponding to the (111) crystal plane fitted by a Gaussian function, and a difference between the first half-width and the second half-width are obtained; Among them, according to the difference between the first half-width and the second half-width being less than 0.4 degrees, the precious metal catalyst that meets the XRD spectrum requirements is screened out.

2. The screening method according to claim 1, wherein The screening method further comprises: obtaining a theoretical ECSA, a measured ECSA, and a difference between the theoretical ECSA and the measured ECSA of the noble metal catalyst that meets the XRD spectrum requirements; Among them, the noble metal catalyst that meets the requirements is screened out based on the absolute value of the difference between the theoretical ECSA and the measured ECSA divided by the theoretical ECSA being less than 5%.

3. The screening method according to claim 1 or 2, characterized in that The noble metal catalyst is a platinum-carbon catalyst, and the loading mass of platinum in the platinum-carbon catalyst is 40%-65%.

4. The screening method according to claim 3, wherein The specific surface area of ​​the platinum-carbon catalyst is 400 m² / g-1000 m² / g.

5. A noble metal catalyst, characterized in that The noble metal catalyst includes a platinum catalyst, a gold catalyst, a palladium catalyst, a platinum-carbon catalyst, a gold-carbon catalyst or a palladium-carbon catalyst; In the XRD spectrum of the precious metal catalyst, the diffraction peak corresponding to the (111) crystal plane of the precious metal has a first half-width, and the diffraction peak corresponding to the (111) crystal plane fitted by the Gaussian function has a second half-width, and the difference between the first half-width and the second half-width is less than 0.4 degrees.

6. The noble metal catalyst according to claim 5, characterized in that The absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA is less than 5%.

7. The noble metal catalyst according to claim 5, characterized in that A difference between the first full width at half maximum and the second full width at half maximum is less than or equal to 0.2 degrees.

8. The noble metal catalyst according to claim 5, characterized in that The absolute value of the difference between the theoretical ECSA and the measured ECSA of the precious metal catalyst divided by the theoretical ECSA is less than or equal to 3%.

9. The noble metal catalyst according to any one of claims 5 to 8, characterized in that The noble metal catalyst is a platinum-carbon catalyst, wherein the average particle size of the platinum particles is 2.5 nm to 4 nm; and / or, The platinum loading mass in the platinum-carbon catalyst is 40%-65%; and / or, The specific surface area of ​​the platinum-carbon catalyst is 400 m² / g-1000 m² / g.

10. A membrane electrode, characterized in that: The method comprises a noble metal catalyst obtained by screening using the screening method according to any one of claims 1 to 4, or a noble metal catalyst according to any one of claims 5 to 9.